Relación de niveles de glicemia basal y hemoglobina glicosilada en pacientes que acuden al Hospital Regional de Ayacucho, 2018. - Cardenas Rodriguez, Flor Milagros (2019)
Objective: To determine the correlation between blood glucose and glycosylated hemoglobin values in patients who attend the Ayacucho Regional Hospital between January 2018 to December 2018. Methodology: It was designed as a descriptive, cross-sectional, non-causal, retrospective, retrospective study conducted at the Regional Hospital of Ayacucho, the year 2018; Of the 783 patients' medical records, 616 contained the complete data and 167 medical records were excluded due to lack of data; collecting data on sex, age group, marital status, level of education, glucose results, results of glycosylated hemoglobin, diagnosis of pathology, symptomatology of diabetic and non-diabetic pathologies; the data obtained were statistically evaluated for which the absolute and percentage frequency distributions were performed and the statistical test of Chi square, mean and standard deviation was performed. Results: According to demographic characteristics such as (sex, age group, level of education and marital status); What predominated in this study was the female sex with 406 cases that represented 65.9%, the male sex with 210 cases that represented 34.1%. Adults who are between 25 and 60 years old with 330 cases that accounted for 53.6%, elderly patients with more than 60 years with 213 cases that accounted for 34.6%. The married are 259 cases representing 42.0% and single with 211 cases representing 34.3%. The level of primary education with 207 cases that represented 33.6% and 189 patients who have no education that represented 30.7% of a total study of 616 patients diagnosed with diabetes and non-diabetes pathology. Regarding the results such as (glycosylated hemoglobin, basal glucose, diagnosis of the pathology and symptoms of diabetic and non-diabetic pathologies). When relating diabetic pathologies to glycosylated hemoglobin levels, type II diabetes is 227 cases greater than 6% up to 14%, type I diabetes with 113 cases, gestational diabetes with 16 cases. And when relating non-diabetic pathologies to glycosylated hemoglobin levels, there are 210 cases that have other pathologies. When performing X2, statistical significance was found (p <0.05), which indicates that diabetic pathologies are related to glycosylated hemoglobin levels greater than 6% to 14%. When the diabetic and non-diabetic pathologies are related to the basal glucose levels, the other pathologies are 195 cases out of a total study of 264 cases of patients who had glycosylated hemoglobin less than 6%. When performing the X2 statistical test, it was determined that there is no statistical association (p> 0.05), which indicates that diabetic pathologies are not related to glycosylated hemoglobin levels less than 6%. When relating the diabetic and non-diabetic pathologies, with other symptoms of diabetes, there are 168 cases that represented 27.3%, polyuria 95 cases that represented 15.4%, other symptoms of other pathologies with 146 cases that represented 23.7% of a total study of 616 patients. Conclusions: The tests of glycosylated hemoglobin and basal glucose are related in diabetic pathologies with great value for the early detection of diabetic pathologies and their use should be recommended in all health establishments in the country.